1993
DOI: 10.1200/jco.1993.11.10.1879
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of leucovorin-modulated fluorouracil as postoperative adjuvant therapy for primary colon cancer: results from National Surgical Adjuvant Breast and Bowel Project protocol C-03.

Abstract: Treatment with LV + 5-FU significantly prolongs disease-free survival and results in a significant benefit relative to overall survival. These findings, when considered together with results from a recent meta-analysis demonstrating a benefit from LV + 5-FU in advanced disease, provide evidence to support the concept of metabolic modulation of 5-FU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
234
1
8

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 625 publications
(249 citation statements)
references
References 17 publications
6
234
1
8
Order By: Relevance
“…Unfortunately, steady-state plasma 5FU levels do not correlate with toxicity (Jodrell et al, 2001) and hence pharmacokinetic monitoring is not used to identify patients who are at increased risk of toxicity (Tebbutt et al, 2000). In randomised controlled trials, dose reductions are common after the first two cycles and 15 -30% of patients fail to complete chemotherapy (Wolmark et al, 1993;O'Connell et al, 1997;Poplin et al, 2005). The relationship between systemic exposure and treatment efficacy has not been demonstrated, however, and can only be ascertained by conducting prospective randomised studies that compare a targeted dose adjustment to a fixed dose (Milano et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, steady-state plasma 5FU levels do not correlate with toxicity (Jodrell et al, 2001) and hence pharmacokinetic monitoring is not used to identify patients who are at increased risk of toxicity (Tebbutt et al, 2000). In randomised controlled trials, dose reductions are common after the first two cycles and 15 -30% of patients fail to complete chemotherapy (Wolmark et al, 1993;O'Connell et al, 1997;Poplin et al, 2005). The relationship between systemic exposure and treatment efficacy has not been demonstrated, however, and can only be ascertained by conducting prospective randomised studies that compare a targeted dose adjustment to a fixed dose (Milano et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, chemotherapy using 5-fluorouracil and leucovorin (5-FU/LV) has become standard treatment for stage III colon cancer after successful surgery. 3,4 However, this chemotherapy is still insufficient for patients at a high risk to recurrence who have biologically aggressive tumors, and the need to improve the outcome in such patients has increased the interest in developing more intensive or more targeted therapeutic strategies.It has been shown that solid tumor growth beyond a certain size requires neovascularization to supply the tumor with oxygen and nutrients. 5 In other words, without neovascularization, micrometastasis cannot grow.…”
mentioning
confidence: 99%
“…While adjuvant radio-and chemo-therapy have improved recurrence-free survival (O'Connell and Gunderson, 1992;Wolmark et al, 1993;Kohnewompner et al, 1994;Schmoll, 1994), these combinations fail to have a significant effect either in those patients who present with Dukes' stage B disease, or on overall patient survival. Since only a minority of patients benefit from the adjuvant treatment modalities, better selection of those at high risk of recurrence, who would gain the major benefits from adjuvant treatment is required.…”
mentioning
confidence: 99%